Perceived Importance and Bundles of Ecosystem Services in the Yangtze River Middle Reaches Megalopolis, China - Zhang, Guanshi; Zhang, Xiu; Xie, Long; Zhang, Qi; Liu, Dongsheng; Wu, Hongjuan; Li, Sen (Frontiers in Environmental Science, 2021)
In this study, a survey with 4,580 residents in the Yangtze River Middle Reaches Megalopolis, central China, was conducted to assess the perceived importance of local ESs. Then, principal component analysis was used to identify their perceived coincidence (i.e., ES bundles), and an automatic linear model was used to reveal how the perceived ES importance and ES bundles were associated with socioenvironmental factors, including demographics, environmental awareness, and living environment. Our results showed that the provisioning ESs, especially water supply, had relatively higher perceived importance. There was no significant difference in perceived ES importance and ES bundles between experts and ordinary residents; thus, experts may recommend practices that meet the local residents’ wishes in the YRMRM. In addition, we disclosed three bundles of perceived ES (i.e., green environment service bundle, ecological stability service bundle, and grain service bundle), which encompassed ES from different ES categories. Potential tradeoff existed in different ES bundles, mainly due to the divergent preferences of different residents. For example, residents with more bus services near the residence tended to perceive green environment service bundle as more important, but perceive ecological stability service bundle as less important. This study adds important first-hand empirical data to the field of the public preferences of local residents for a region of high economic and ecological importance in China, which could provide more information and scientific basis for socially just and sustainable region environmental planning and management.